Comparative Gene Expression and Physiological Analyses Reveal Molecular Mechanisms in Wound-Induced Spore Formation in the Edible Seaweed Nori - Guan, Xiaowei; Mao, Yunxiang; Stiller, John W.; Shu, Shanshan; Pang, Ying; Qu, Weihua; Zhang, Zehao; Tang, Fugeng; Qian, Huijuan; Chen, Rui; Sun, Bin; Guoying, Du; et al. (Frontiers in Plant Science, 2022)
Genetic reprogramming of differentiated cells is studied broadly in multicellular Viridiplantae as an adaptation to herbivory or damage; however, mechanisms underlying cell development and redifferentiation are largely unknown in red algae, their nearest multicellular relatives. Here we investgate cell reprogramming in the widely cultivated, edible seaweed Neopyropia yezoesis (“nori”), where vegetative cells in wounded blades differentiate and release as large numbers of asexual spores. Based upon physiological changes and transcriptomic dynamics after wound stress in N. yezoensis and its congener Neoporphyra haitanensis, another cultivar that does not differentiate spores after wounding, we propose a three-phase model of wound-induced spore development in N. yezoensis. In Phase I, propagation of ROS by RBOH and SOD elicites systematic transduction of the wound signal, while Ca2+ dependent signaling induces cell reprogramming. In Phase II, a TOR signaling pathway and regulation of cyclin and CDK genes result in cell divisions that spread inward from the wound edge. Once sporangia form, Phase III involves expression of proteins required for spore maturation and cell wall softening. Our analyses not only provide the first model for core molecular processes controlling cellular reprogramming in rhodophytes, but also have practical implications for achieving greater control over seeding in commercial nori farming.